Research Trends in Class II Malocclusion Treatment in Growing Individuals: A Bibliometric Study - Lo Giudice, Antonino; Boato, Mattia; Palazzo, Giuseppe (International dental journal, 2025)
This study aims to perform a bibliometric analysis of the literature on correction of Class II malocclusion in growing individuals by evaluating the evolution and current state of treatment and to predict future research hot spots and trends. Keyword queries were used to search for articles in the Web of Science Core Collection at the electronic library of University of Catania. The resulting literature data were imported into CiteSpace 6.3.R1 and VOSviewer software to analyse authorship, countries, institutions, and keywords and to perform cluster analysis. A total of 843 articles were analysed. Research in this field has shown a consistent and ongoing publication trend on the addressed topic, with a significant increase in the last decade, attributed to growing interest in skeletal anchorage. The institutions in the United States, Italy, and Brazil contributed predominantly to the investigated subject area. Class II correction in growing individuals using functional appliances or headgears has gained widespread attention and popularity due to the potential to counteract unfavourable maxillary and/or mandibular growth patterns, improving skeletal disharmony and facial attractiveness. A specific geographic publication trend was found for functional appliances and headgears that may represent an ethical and racial bias . Both of the latter approaches are effective in reducing the overjet. However, the primary rationale for early intervention is reducing the risk of incisal trauma and bullying episodes at childhood